(untitled) (Research, Society and Development, 2020)
The increasing increase in agro-industrial production is causing concern about the amount of waste generated. However, these wastes can be used as value-added by-products. Thus, this work aimed to develop an alternative to use of pearl variety pineapple residue in cookie. Cookie formulations were made with 5% (A), 10% (B) and 15% (C) flour from dehydrated pineapple shells in relation to the wheat flour used. Sensory attributes (color, taste, texture, appearance and aroma) were evaluated using a 9 point hedonic scale and purchase intent with a 7 point scale. Results were submitted to Tukey test at 5% significance level. The acceptance index was applied to verify the best product and analyzed for the physical, chemical and centesimal composition characteristics, performed in triplicate. Cookie B obtained an average score above 7 points for all sensory attributes and an average of 5.43 in the tasters’ attitude profile test, with the highest acceptance rate (85.53%). There was an increase in the diameter and thickness of cookie B, which yielded about 80%. The product complies with acidity, gray and moisture legislation and can be considered a food as high fiber content.